2019
DOI: 10.1136/bmjsrh-2018-200236
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year evaluation of the emergency contraception enhanced community pharmacy service provided in Wales

Abstract: BackgroundAccess to emergency contraception (EC) has been a core component of attempts to address high teenage pregnancy rates in Wales. A national service was commissioned in 2011, allowing supply of EC free of charge from community pharmacies (CPs). This study investigated 5 years of the EC service, to describe its use and investigate changes in the pattern of use over time.MethodsSecondary analyses of data from all National Health Service funded CP EC consultations in Wales between 1 August 2012 and 31 July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…69 75 77 79 Mantzourani et al noted that 31% of EC consultations included a referral to a sexual health clinic or a general practitioner. 77 Monastersky Maderas and Landau found that pharmacy and clinic partnerships to expand access to injectable contraception resulted in reciprocal referrals. 75 Michie et al concluded that referral by pharmacists to a family planning clinic and pharmacists' provision of progestogen-only contraceptive pill were valuable and could increase the uptake of effective contraception after EC.…”
Section: Contraceptionmentioning
confidence: 99%
“…69 75 77 79 Mantzourani et al noted that 31% of EC consultations included a referral to a sexual health clinic or a general practitioner. 77 Monastersky Maderas and Landau found that pharmacy and clinic partnerships to expand access to injectable contraception resulted in reciprocal referrals. 75 Michie et al concluded that referral by pharmacists to a family planning clinic and pharmacists' provision of progestogen-only contraceptive pill were valuable and could increase the uptake of effective contraception after EC.…”
Section: Contraceptionmentioning
confidence: 99%
“… 6 This finding highlights the potential for providing bridging contraception within retail settings, such as community pharmacies, to reduce repeat emergency contraception use and unintended pregnancies in this group. 35 Importantly, the mean age of women participating in the Bridge-it study was 22 years, highlighting that the intervention reached key age groups; abortion rates in the UK are highest among women aged 20–24 years 30 , 31 and use of emergency contraception highest among women aged 16–24 years. 6 Thus, if the Bridge-it intervention were implemented widely as a service, the use of effective contraception might increase in the relevant age group and among those at greater risk of unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, media campaigns to improve awareness of contraception and LARC among young people were introduced in November 2009; however, this only ran for a month, and it was unlikely that the impact lasted as long as the end of our study period in 2013/2014 [ 27 ]. In addition, the Teenage Pregnancy Strategy was introduced in England in 1999, and the policy was implemented for 10 years [ 28 ]; emergency hormonal contraception had been made available free of charge in Scotland from 2008 and in Wales in 2011, which could also contribute to reducing unplanned pregnancies [ 29 , 30 ]. However, our study design shows additional impact of the P4P scheme over underlying trends and in other age groups.…”
Section: Discussionmentioning
confidence: 99%